Influence of Dietary Changes in Roughage: Concentrate Ratio and Feed-Fodder Prices on Profitability of Commercial Dairy Farm - Thakur, Arti; Sirohi, Smita; Oberoi, P. S. (Indian Journal of Animal Nutrition, 2018)
Feed is the major input factor in all livestock production systems. The productivity of livestock is strongly related to the feed resource availability. There is scarcity of feeds and fodders in our country and prices of feeds and fodders are increasing continuously. So efficient use of feed resources is important. Simulation is done to know the effect of change in prices on project viability. Simulation of feeds quantity and prices was done for herd of 100 animals. Prices of the feed/fodder have negative effect on project profitability. As roughage concentrate ratio changed from baseline 60:40 to 50:50; it increased the daily feed cost by Rs. 23-24/d/animal. Benefit Cost ratio changed from 1.48 to 1.46 which was not significant. In case of internal rate of return there was one % point decline from 54 % to 53 %. If the roughage concentrates ratio changed from 60:40 to 70:30, it led to decrease in cost of feed by Rs.13-15/d/animal. This study revealed that both prices and quantity have inverse relation with project profitability.